Uptalk, Vocal Fry and, Like, Totally Slang: Assessing Stylistic Trends in American Speech - Lewandowski, Tadeusz (Stylistyka, 2020)
This paper examines linguistic debates surrounding new stylistic conventions in American English, namely the use o f uptalk (speaking statements with a sing note at the end, as in a question), vocal fry (the injection o f creaky, glottal vibrations at the end o f words), and the increasing appearance o f slang in the United States school system. These phenomena are assessed through the prism o f Dwight Macdonald’s essays on English from the l°60s, and the “prescriptive” vs. “descriptive” debate on lexicography bom in that ame decade. While this division of perspectives and defines the rift from past models of language and culture, the current prevalence of the descriptiv e school in American academia and its endorsement of uptalk, vocal fry, and slang designate the trajectory of English’s stylistic future.